USING INTERACTIVE METHODS IN TEACHING THE TOPIC “HALOGENS” - Khodzhanazarova , Nilufar; Eshchanov , Ruzumboy; Ataullaev, Zokir (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
In the field of chemistry education, particularly when teaching the topic of halogens, the use of interactive methods plays a crucial role in enhancing lesson effectiveness. Modern educational systems emphasize the integration of innovative pedagogical technologies to make the learning process more engaging, productive, and active. Interactive teaching methods encourage students to develop independent thinking, as well as creative and critical thinking skills, which are essential for mastering complex scientific concepts